1985
DOI: 10.1177/000992288502401001
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Disorder Children with or without Hyperactivity

Abstract: Each patient with Attention Deficit Disorder (ADD), with or without hyperactivity, is unique in the variety and severity of the handicapping conditions associated with ADD. The use of a well-designed teacher rating scale can provide the clinician with a behavioral profile of each patient. The importance of knowing the child's specific problems is emphasized by the results of this research, which show that methylphenidate has a major effect in improving attention, is helpful in decreasing activity level, but of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…First, there are, at present, only a few studies available comparing the effectiveness of stimulant medication in the treatment of different subtypes of ADHD. The results of these studies suggest that patients of all subtypes of ADHD tend to respond positively to stimulant medication (Barkley et al 1990;Famularo and Fenton 1987;Saul and Ashby 1986;Sebrechts et al 1986;Stein et al 2003;Ullmann and Sleator 1985), although children with ADHD-I displayed less additional benefit from higher doses of MPH than children with ADHD-C (Stein et al 2003). Second, the small sample size of the ADHD-I group prevented statistical analysis of group differences.…”
Section: Participantsmentioning
confidence: 99%
“…First, there are, at present, only a few studies available comparing the effectiveness of stimulant medication in the treatment of different subtypes of ADHD. The results of these studies suggest that patients of all subtypes of ADHD tend to respond positively to stimulant medication (Barkley et al 1990;Famularo and Fenton 1987;Saul and Ashby 1986;Sebrechts et al 1986;Stein et al 2003;Ullmann and Sleator 1985), although children with ADHD-I displayed less additional benefit from higher doses of MPH than children with ADHD-C (Stein et al 2003). Second, the small sample size of the ADHD-I group prevented statistical analysis of group differences.…”
Section: Participantsmentioning
confidence: 99%
“…• Attention, Impulsivity, and Activity Level. Several tools were used to evaluate attention, including (a) the ADD-H Comprehensive Teacher's Rating Scale (ACTeRS) (Ullmann, Sleator, & Sprague, 1991), which is effective in discriminating between children with and without attention disorders (Ullmann & Sleator, 1985Ullmann, Sleator, & Sprague, 1984); (b) three subtests of the Leiter International Performance Scale-Revised: Parent Rating Scale (Roid & Miller, 1997), which has an excellent national standardization and impressive reliability and validity characteristics; (c) Barkley's Behavior Rating for…”
Section: Instrumentation: Research Questionmentioning
confidence: 99%
“…It is difficult to evaluate these results because of the lack of standard diagnostic criteria, and because it is not clear how decisions about changing dosage were made or what specific criteria were used for defining "responders." Ullman and Sleator (1985) reported that a group of 86 children with ADD, including 13 with ADD/WO, showed significant improvements on ACTeRS ratings on .3, .5, or .8 mg/kg methylphenidate when compared to placebo. Again, it is impossible to draw conclusions from this study, because the criteria for diagnosing ADD/WO are unclear (although diagnoses were evidently based on ACTeRS scores) and because results from children with ADD/WO and ADD/ H children were not distinguished and compared.…”
Section: Comparison Of Effects Of Stimulant Medication For Add/wo Andmentioning
confidence: 99%
“…Since the publication of DSM-III in 1980, however, a total of 222 clinicreferred children who meet DSM-III criteria for ADD/WO have been described in research articles and presentations (Berry, Shaywitz, & Shaywitz, 1985;Carlson, Alvarez, & Needleman, 1989;Conte, Kinsbourne, Swanson, Zirk, & Samuels, 1986;Edelbrock, Costello, & Kessler, 1984;Famularo & Fenton, 1987;Frank & Ben-Nun, 1988;Hynd, Lorys, Semrud-Clikeman, Nieves, Huettner, & Lahey, in press;Hynd et al, 1988;Lahey, Schaughency, Hynd, Carlson, & Nieves, 1987;Maurer & Stewart, 1980;Saul & Ashby, 1986;Ullman & Sleator, 1985). Ninety-seven children considered to have ADD/WO according to experimental criteria based on DSM-III have also been identified in school-based samples (Barkley, DuPaul, & McMurray, in press, 1990;Carlson, Lahey, & Neeper, 1986;King & Young, 1982;Lahey, Schaughency, Strauss, & Frame, 1984;Sargeant & Scholten, 1985a).…”
mentioning
confidence: 99%